The Relationship Between Private Investment and Government Investment After Economic Liberalization - Jesukumar, K.; Uthayakumar, S.S. (University of Jaffna, 2018)
Investment is an important element of the development of the economy in which the private investment is considered as the key engine of economic growth of developed and developing countries. Empirical studies suggest that there number factors influencing the private investment. Open Economic policies introduced in 1977 have influenced the private investment in Srilanka. This research is focused on finding the relationship and effect between private investment and public investment after the economic liberalization. This study used secondary data which are time series data collected from various sources of Central Bank Annual Reports and magazines. Data for this research covered the data from 1977 to 2016. Multiple Regression Analysis was used to estimate the impact. Estimation method was Ordinary Least Squares(OLS). EViews 9 econometrics software were used for data analysis The empirical evidence shows that there is a statistically significant positive impact of selected economic variables on the private investment. Further, this research has identified various problems faced in attracting private investment and public investment including ideal sector identification and the appropriate recommendations have been presented in order to realize the major benefits from the private and government investment in the country.
Keywords: Private Investment; Government Investment; Foreign Direct Investment